Monitoring the dynamics of the surface deformation prior to the onset of plasma emission during femtosecond laser ablation of noble metals by time-resolved reflectivity microscopy - Carrasco Garcia, Irene M.; Vadillo-Pérez, José Miguel; Laserna-Vázquez, José Javier (Elsevier, 2017)
The generation of an expanding plasma during laser ablation is preceded at early times by the formation and evolution of a subsurface melted front. The monitoring of such transient event can't be studied by conventional spectroscopic techniques. Pump-probe femtosecond microscopy allows the following of the surface changes during femtosecond laser ablation taking advantage of the formation of a number of dynamic Newton rings that evolve with time. Measurements at different times allow the quantification of the radial expansion velocity of the molten material. For Au and Ag, expansions in the range of 7000–12,000 m/s for Au and 3000–21,000 m/s have been calculated depending on the pump energies. Such values correspond to hypersonic velocities with Mach number between 3 and 6.
Keywords: Ablación láser; Plasma inducido por láser; Femtosecond laser ablation; Pump-probe spectroscopy; Newton rings; Laser-matter interaction